Language endangerment and the linguistic vitality of Miao in China: Cultural shifts and revitalisation strategies - Li M; Croucher S; Shen L (Taylor and Francis Group, 2024)
This study applies ethnolinguistic vitality (EV) theory to analyse the diminishing proficiency and usage of the Miao language among its speakers in Guizhou, China. Forty-five Miao participated in the semi-structured interviews for this project. The study identified the language’s endangered status characterised by low vitality, Mandarin dominance, declining proficiency, and economic-cultural shifts. Media influence exacerbated these threats, while negative perceptions of Miao linguistic capital and inadequate educational resources further endanger the language. Integrating EV theory, this study informs targeted revitalisation efforts crucial for ensuring the sustainability of the Miao language amidst socio-economic pressures favouring Mandarin dominance in China.
Keywords: Ethnolinguistic vitality (EV); Miao Language; language endangerment; Language shift; Shifting attitudes